Liability of healthcare providers towards independent contractors: profiteering vis a vis patients' rights - Jahn Kassim, Puteri Nemie (2013)
With the changing landscape of the labour markets, healthcare providers find themselves assuming new duties and responsibilities to the general public. In an attempt to insulate themselves from liability, healthcare providers are trying to delegate legal duties to staff whom they considered as “independent” of which, they claim to have no control in the manner on how they execute their duties. This is usually done by posted notices at their facilities or statements in the admission documents. This practice has been argued to be against the notion of fairness and justice as the staff employed advances the economic interests of healthcare providers, therefore, healthcare providers should bear the corresponding liability for losses incurred. Further, employers are in a more strategic position to reduce accidents by efficient organisation and supervision of their staff and some duties cannot be divested by delegation even to a reputable contractor.